2012
DOI: 10.1021/jf204273n
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short-Term UVB Exposure on Vitamin D Concentration of Eggs and Vitamin D Status of Laying Hens

Abstract: Vitamin D deficiency in humans is widespread, and only a few food items are important natural sources of vitamin D. This study investigated the effect of UVB exposure of laying hens on the vitamin D content in egg yolk. In a two-factorial design, hens fed a vitamin D-deficient (-D) or -adequate (+D) diet were nonexposed or exposed to UVB light over a period of 4 weeks. UVB exposure of the -D group caused nearly normal egg production rate and egg shell quality; exposure of the +D group did not further improve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…As the synthesis of 25‐OH‐D is rarely regulated, its blood concentrations correlate well with dietary vitamin D intake (Stanford, ). This has also been shown in different studies in poultry (Jiang et al., ; Lietzow et al., ; Tsang & Grunder, ). In contrast, an increase of 1,25‐(OH) 2 ‐D, which has a slow and well‐regulated synthesis, could only be observed in white Leghorn hens when supplementing 1,100 IU vitamin D/kg (27.5 μg/kg) to a vitamin D free diet, whereas doubling the vitamin D supplementation did not further increase the plasma concentrations (Tsang & Grunder, ).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…As the synthesis of 25‐OH‐D is rarely regulated, its blood concentrations correlate well with dietary vitamin D intake (Stanford, ). This has also been shown in different studies in poultry (Jiang et al., ; Lietzow et al., ; Tsang & Grunder, ). In contrast, an increase of 1,25‐(OH) 2 ‐D, which has a slow and well‐regulated synthesis, could only be observed in white Leghorn hens when supplementing 1,100 IU vitamin D/kg (27.5 μg/kg) to a vitamin D free diet, whereas doubling the vitamin D supplementation did not further increase the plasma concentrations (Tsang & Grunder, ).…”
Section: Discussionsupporting
confidence: 76%
“…This method was found to be reliable to detect 25‐OH‐D in different species such as cattle, pigs, poultry, mink, horse and humans (Hymoller & Jensen, ). Plasma concentrations of 1,25‐(OH) 2 ‐D were analysed by radioimmunoassay (RIA), a method already used in chickens (Lietzow et al., ; Sedrani, ) or African grey parrots ( Psittacus e erithacus ; Stanford, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…), serum 25 hydroxy‐vitamin D (25(OH)D) levels were measured. Cord and maternal vitamin D concentrations were determined by liquid chromatography tandem mass spectroscopy (HPLC‐MS/MS) by the laboratory of the Institute of Agricultural and Nutrition Science, Martin‐Luther‐University Halle/Wittenberg (Halle/Saale, Germany) as previously described (, ). Briefly, 25(OH)D 3 and 25(OH)D 2 were obtained from standards, cord and maternal serum via protein precipitation using the HPLC‐MS/MS MassChrom Reagent Kit (Chromsystems, Munich, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…We therefore came up with the idea that UVB exposure of farm animals such as laying hens might become a promising option to further improve the vitamin D content of foods from animal origin. In an initial experiment we could show that chickens whose upper part of their body was exposed to UVB did not produce vitamin D-enriched eggs [16]. Current analysis from our research group showed that most of the 7-dehydrocholesterol (7-DHC), the pre-cursor and limiting factor for vitamin D 3 synthesis, was located in the unfeathered skin of the chicken legs.…”
Section: Introductionmentioning
confidence: 97%